Questionable reversal of anticoagulation in the therapeutic management of cerebral haemorrhage associated with vitamin K antagonists - de Leciñana, Maria Alonso; Huertas, Nuria; Egido, Jose A.; Muriel, Alfonso; García, Ana; Ruiz-Ares, Gerardo; Díez-Tejedor, Exuperio; Fuentes, Blanca (Thrombosis and Haemostasis, 2013)
Reversal of anticoagulation is recommended to correct the international normalised ratio (INR) for patients with intracranial haemorrhage (ICH) associated with vitamin K antagonists (VKA). However, the validity of such treatment is debated. We sought to identify, prospectively, the prognostic effect of VKA-ICH treatment in a cohort of patients (n=71; median age 78 years, range 20–89; 52% males). Data collated were: baseline characteristics, treatments, baseline and post-treatment INR, haematoma volume, and haematoma enlargement. Treatment effects and prognostic factor assessment were in relation to mortality and functional outcomes. On admission, the patients had a median score of 9 [p25; p75 of 5; 20] on the National Institute of Health Stroke Scale (NIHSS) and a mean INR of 2.7 (range: 0.9 – 10.8). Haematoma volume (34.6 cm3; SD: 24.9) correlated with NIHSS (r = 0.55; p<0.001) but not with INR. Anticoagulation reversal treatment was administered in 83% of patients. INR <1.5 was achieved in 60.7% of cases. Death or dependency at three months was 76%. Neither baseline INR, anticoagulation reversal nor haematoma enlargement were related to mortality or functional outcome. The only independent prognostic factor was clinical severity on admission. Baseline NIHSS predicted mortality (OR: 1.18; 95%CI: 1.09–1.27), independence (OR: 0.83; 95%CI: 0.74–0.94) and neurological recovery (NIHSS 0–1) (OR: 0.83; 95%CI: 0.73–0.95). The data indicate that VKA-ICH had a poor prognosis. Treatment and INR correction did not appear to affect outcomes.
Keywords: Intracerebral haemorrhage; oral anticoagulants; vitamin K antagonists; prothrombin complex concentrate